Comparative Analysis of Spiral Coil Receiver and Cylindrical Pot like Receiver on the Performance of Parabolic Solar Concentrating System for Thermal Steam Generation. - A. B., Bande; I., Muddasir; A. , Hajara; S. , Muktar (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The technology aspect of solar energy is crucial to solving the current global environmental and energy issues. Scientists, engineers, governmental and non-governmental organizations are becoming more aware of the exciting new potential that is solar concentrating systems for thermal heat energy generating use for residential, commercial, and industrial enterprises. The purpose of the research work was to compare the performance of the Parabolic Solar Concentrating (PDSC) system for thermal steam generation between a spiral coil receiver and a cylindrical pot-like receiver. Materials used to construct the PDSC, SCR, and CPR were stainless steel reflector sheet, copper tube pipe, and aluminum sheet, in that order. To facilitate the rotation of the system in the direction of solar radiation, a basic manual tracking mechanism was used. A limited experimental trial was carried out in different weather circumstances, and the thermal steam produced by the system using SCR and CPR as receiver absorbers was utilized for comparison analysis along with the performance assessment. High temperature steam was found to be produced by the parabolic solar concentrating system using SPR and CPR as receivers, with values of 225.3 OC and 210 OC, respectively. This temperature variation by the two receivers could be as the results of differences in term of material used in construction the receivers’ absorber.